Produção de biomassa e composição química de adubos verdes cultivados no vale do ribeira - Lima, Juliana Domingues [UNESP] (2012)
The contribution of green manure to soil improvement and crop production depends primarily on biomass production and its chemical composition, which vary depending on the species, region and growing season. The aim of this research was to evaluate the chemical composition of biomass produced by green manures in Vale do Ribeira, São Paulo, Brazil. In order to develop this research, was carried an experiment in Pariquera-Açu, in 2006/2007, in completely randomized blocks design with four treatments (three green manure and spontaneous vegetation) and five replications. At 30, 60, 90 and 120 after sowing samples were collected in 1m2 of the shoots and determined fresh and dry, and chemical composition biomass. Sunhemp, pigeon pea and mucuna produced, in decreasing order, the largest quantities of biomass and were more efficient than the spontaneous vegetation. The biomass produced by green manure had higher quality than that produced by spontaneous vegetation. Sunhemp and pigeon pea have a higher proportion of dry matter in stems which have low N, high C/N and L/N ratio, variables indicating slow decomposition of residues. The analysis of dry matter partitioned to better indication of the chemical composition of the residues and the prevision of the availability of nutrients in the soil.